Air pollution-induced health impacts and health economic losses in China driven by US demand exports. (15th December 2022) - Feng, Tian; Chen, Hongwen; Liu, Jianzheng
Abstract: Understanding how trade between regions or countries drives the transfer of air pollution has attracted considerable interest recently, but few studies have explored the various transfer pathways or evaluated economic losses due to the health impact of such air pollution. Here, we assess the air pollutant emissions and related health impacts and economic losses in China caused by export trade due to US demand by combining the linked multi-regional input-output (MRIO) model, GEOS-Chem model, integrated exposure-response model, and the willingness to pay method. We show that the air pollutant emissions embedded in China's export due to the US demand reached 5792.38 Kt in 2012 (2.48% of the total), which includes direct exports of intermediate (40.27%) and final (33.61%) products and indirect exports of intermediate products via domestic provinces (16.43%, domestic spillover) and other countries (9.69%, foreign spillover). The resulting increase in PM2.5 (<2.8 μg m −3 ) leads to additional 27, 963 deaths in 30 provinces, with a higher death toll in coastal areas and the corresponding economic loss was higher in more developed regions and reached USD 2.08 billion. This study highlights the region-different air pollution and health impacts in China embedded in the US-demand trade, and provides a framework for the analysis of health and economic losses hidden in global trade, particularly between developing and developed countries. Graphical abstract: Image 1 Highlights: Air pollution and health impacts in China driven by US-demand exports were assessed. The PM2.5 increase led to 27, 963 deaths in China, with more deaths in coastal areas. The related economic losses were higher in more developed regions of China.